Strategy to Increase Competitiveness of Tourism Sector MSMEs in Parepare - Firmasyah Firmasyah; Abdul Rahman Laba; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
The research aims to identify internal and external factors as well as strategies to increase the competitiveness of the tourism sector in the tourism sector in Parepare City. The research was conducted in the City of Parepare. The number of samples is 30 MSMEs managers in the tourism sector and informants in the tourism industry in the City of Parepare. Data collection was carried out through observation, documentation, interviews, and questionnaires. Data were analyzed by using a qualitative descriptive approach with SWOT and AHP analysis. The results show that the highest score is on the strength factor of a technology-based room reservation system, the quality of raw materials, and the characteristics of local products. Weakness factors are not having a tourism business certification, product prices are less affordable, and the minimal use of technological tools. Opportunity factors are synergy among hoteliers, increasing tourists, and developing marketing locations. The threat factors for tourism competition among regions, the number of competitive processed products, and product competition. The results of the AHP method show the priority criteria to achieve the main focus. The factor level is human resources, the actor level, namely the Department of Manpower. The level of priority objectives, namely, the quality and productivity of the tourism MSMEs in the tourism sector. The alternative priority strategy that is implemented is to form a training forum for MSMEs in the tourism sector, utilize training and production equipment assistance, and develop tourism packages and digital technology so that it will have an impact on increasing the competitiveness of SMEs in the tourism sector in the city of Parepare.